Auditoria Financiera Al Área De Salud N° 12 De Vilcabamba Del Canton Loja Periodo 01 De Enero Del 2010 Al 31 De Diciembre Del 2012 - Ortega Diaz, Jessica Alexandra (2016)
Thesis entitled “FINANCIAL AUDIT AREA HEALTH No.12 VILCABAMBA PERIOD FROM 01 JANUARY 2010 TO DECEMBER 31, 2012," was developed based on the objectives. For the preparation of the thesis and the scientific methods applied allowed to establish and deepen the problems and phenomena of reality with a reflective position , critical and positive, the inductive method was used to gain knowledge of particular facts based on the general knowledge used laws , deductive served to identify compliance with the standard , with analytical Their implementation will analyze the accounts of the account balances to determine the reasonableness thereof , mathematician Facilitated make such calculations and operations related to financial information obtained from the entity , allowed us to tell descriptive narrative and finally synthetic served to carry the report of findings cedulas. Also use materials that facilitated the implementation of the same, as those techniques and procedures to serve as support for a clear and specific research. Among the results it was found that the source of the entity no documentation is printed and duly ordained and the financial staff does not meet the job profile.